Etika Bisnis Islam Memoderasi Pengaruh Tarif dan Persaingan Bisnis Terhadap Kesejahteraan Sopir Berbasis di Kota Parepare - Aldi Jayansyah; Arwin Arwin; Zainal Said; Sulkarnain Sulkarnain (MARGIN ECO, 2026)
This study examines the role of Islamic business ethics in moderating the influence of tariffs and business competition on the welfare of intercity public transportation drivers in Parepare City. Using a quantitative approach with an associative research design, data were collected from 100 respondents through purposive sampling techniques. The data were obtained using Likert-scale questionnaires and analyzed using PLS-SEM. The results indicate that tariffs (β = 0.342; p < 0.05) and business competition (β = 0.369; p < 0.05) have a positive and significant effect on drivers’ welfare. In contrast, Islamic business ethics does not have a significant effect either directly or as a moderating variable (p > 0.05). This condition occurs because the practice of Islamic business ethics among drivers has not been implemented consistently and remains limited to conceptual understanding rather than practical application. The R² value of 0.230 indicates that the model explains only a small proportion of the variation in welfare, suggesting that other factors outside the model still play a more dominant role. These findings imply that economic factors, such as tariffs and competitive dynamics, are more influential in determining drivers’ welfare than normative factors. This study provides important implications for the formulation of fair and sustainable tariff policies and competition management.